Development of Quizizz-based Interactive Learning Media and Assessment to Enhance Critical Thinking Skills in Avionic Training - Hardinata Hardinata; Yayat Ruhiyat; Lukman Nulhakim; Cucu Atikah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Modern aircraft maintenance requires technicians to demonstrate higher-order thinking skills (HOTS) to diagnose and resolve complex avionic system failures. However, assessment practices in vocational avionic training often emphasize procedural recall rather than analytical and evaluative reasoning. This study addresses this gap by developing and evaluating Quizizz-based interactive learning media and HOTS-oriented assessments tailored to avionic training contexts. A research and development approach employing the ADDIE model was implemented using a pre-experimental one-group pretest–posttest design. The study involved 22 avionic trainees at the Lion Group Training Center, Tangerang. Data were collected through expert validation, trainee questionnaires, interviews, and pretest–posttest assessments. Statistical analyses included normality testing, paired-sample t-tests, and N-Gain analysis. Expert validation indicated high feasibility of the developed media, with acceptance rates of 83% from media experts and 88% from material experts, while trainee responses reached 86%. Descriptive statistics showed a substantial increase in posttest mean scores compared to pretest results. The paired-sample t-test revealed a statistically significant improvement in critical thinking skills (p 0.05). The N-Gain score (mean = 0.58) indicated a moderate-to-high level of learning improvement. The findings suggest that scenario-based, gamified assessments delivered through Quizizz effectively support the development of critical thinking skills in avionic training. This study highlights the potential of integrating HOTS-oriented digital assessments in vocational education while recommending further multi-site and longitudinal research to strengthen generalizability.